Bacterial diversity assessment of pristine mangrove microbial community from Dhulibhashani, Sundarbans using 16S rRNA gene tag sequencing - Basak, Pijush (Genom Data, 2015)
The global knowledge of microbial diversity and function in Sundarbans ecosystem is still scarce, despite global advancement in understanding the microbial diversity. In the present study, we have analyzed the diversity and distribution of bacteria in the tropical mangrove sediments of Sundarbans using 16S rRNA gene amplicon sequencing. Metagenome is comprised of 1,53,926 sequences with 108.8 Mbp data and with 55 ± 2% G + C content. Metagenome sequence data are available at NCBI under the Bioproject database with accession no. PRJNA245459. Bacterial community metagenome sequences were analyzed by MG-RAST software representing the presence of 56,547 species belonging to 44 different phyla. The taxonomic analysis revealed the dominance of phyla Proteobacteria within our dataset. Further taxonomic analysis revealed abundance of Bacteroidetes, Acidobactreia, Firmicutes, Actinobacteria, Nitrospirae, Cyanobacteria, Planctomycetes and Fusobacteria group as the predominant bacterial assemblages in this largely pristine mangrove habitat. The distribution of different community datasets obtained from four sediment samples originated from one sampling station at two different depths providing better understanding of the sediment bacterial diversity and its relationship to the ecosystem dynamics of this pristine mangrove sediment of Dhulibhashani in, Sundarbans.